Should IKEA Expand into Brazil: A Study of Brazilian Consumer Behaviours - Hiroshi Ito; Nada Alelweet; Rebecca Harrison; Alice Mitchell; Ellis Parker (International Journal of Economics and Financial Issues, 2014)
IKEA, a Swedish furniture company, is considering entering the Brazilian market. This paper examines whether or not IKEA might be successful in the Brazilian market by reviewing the following issues: the growth of middle class, consumer spending, internet usage and eco-awareness. This study finds that the growing middle class in the country and the increasing average household disposable income is a promising sign that the ability of consumers to afford IKEA products is increasing. The growing online presence of Brazilian consumers is also a positive aspect of IKEA's potential move into the market as it would enable consumers to browse and purchase product via the internet in accordance with current company practices.  Brazilian consumers are currently involved in a trend that favours eco-friendly companies such as IKEA. The paper concludes that IKEA would be received favourably among customers within the market.